Implementation of a Multi-Modal Palliative Care Curriculum for Pediatric Residents. (November 2021) - Romanos-Sirakis, Eleny; Demissie, Seleshi; Fornari, Alice
Objectives: To evaluate the feasibility and efficacy of a new multi-modal pediatric palliative care curriculum. We sought to determine the effect on comfort in palliative care, knowledge, and change in behavior by utilizing these skills with patients, and determine which modalities were most effective for residents. Study Design: 25 pediatric residents were exposed to the 4-part curriculum. The modalities utilized in this curriculum included didactics, role-play, videos, case-discussion, small group activities, simulation, poetry and reflection. Results: The pediatric residents self-reported an increase in comfort and knowledge of the components of pediatric palliative care after this curriculum. In addition, 74% of residents were able to identify a patient experience in which a component of the palliative care curriculum was utilized directly in patient care. The effectiveness of techniques utilized in this multimodal curriculum varied; residents reported that the poetry and reflection components were less effective, as compared with the role-play, simulation and other active learning components. Conclusions: Implementation of a multi-modal palliative care curriculum was effective in increasing knowledge in palliative care, comfort in breaking bad news, and caring for patients with palliative care needs. This can be translated into a change in behavior to utilize these new skills in the care of various patients in pediatrics. Among the various techniques used to teach this curriculum, residents reported that the techniques that most incorporated active learning and were directly applicable to the professional role of the resident were rated most valuable. This curriculum was well received, feasible and effective for pediatric residents.